Nonlinear optical properties of metal nanoparticles: a review - Zhang, Yu-xi; Wang, Yu-hua (RSC advances, 2017)
Metal nanoparticles (MNPs) hold great technological promise because of the possibility of engineering their electronic and optical properties through material design. One of the effective methods to fabricate MNPs is ion implantation. In this review, recent results on the nonlinear optical properties of nanoparticles (including copper, silver, gold, and bismuth nanoparticles) doped in various bases have been discussed. Some specific optical nonlinear properties, such as nonlinear refraction, two-photon absorption, and optical limiting, for femtosecond, picosecond, and nanosecond laser pulses have also been covered. In addition to ion implantation, we have summarized several other methods for the preparation of composite materials, and Z-scan has been used to study the nonlinear optical properties of these materials. Metal nanoparticles (MNPs) hold great technological promise because of the possibility of engineering their electronic and optical properties through material design.